Wild [videorecording (DVD)] - Vallée, Jean-Marc; Witherspoon, Reese, 1976-; Dern, Laura; Sadoski, Thomas, 1976-; Strayed, Cheryl, 1968-; Strayed, Cheryl, 1968- (20th Century Fox Home Entertainment, 2015)
After years of reckless behavior, a heroin addiction and the destruction of her marriage, Cheryl Strayed makes a rash decision. Haunted by memories of her mother Bobbi and with absolutely no experience, she sets out to hike more than a thousand miles on the Pacific Crest Trail all on her own.